2007
DOI: 10.2134/agronj2006.0074
|View full text |Cite
|
Sign up to set email alerts
|

Defoliation Effects on Production and Nutritive Value of Four Irrigated Cool‐Season Perennial Grasses

Abstract: Irrigated cool‐season perennial grasses are becoming an important complementary forage source in the Central Plains. A study was conducted to evaluate effects of clipping stubble height on dry matter (DM) production, growth rate, tiller density, and nutrient content of smooth bromegrass (Bromus inermis Leyss.) orchardgrass (Dactylis glomerata L.), creeping foxtail (Alopecurus arundinaceus Poir.), and meadow bromegrass (Bromus riparius Rhem.) under irrigated conditions on a Cozad silt loam soil (fine‐silty, mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 30 publications
5
26
4
Order By: Relevance
“…Cutting to 5 cm resulted in the highest yields in this system for both pure orchardgrass and the orchardgrass/alfalfa mixture over 3 years. It is clear that harvesting to a low cutting height will remove a greater proportion of aerial biomass and this has been shown in several experiments with orchardgrass where yields were greater at lower cutting heights (Brink et al., ; Mitchell, ; Raese & Decker, ; Sprague & Garber, ; Volesky & Anderson, ). Low cutting heights, however, remove a greater proportion of photosynthetic leaf area and non‐structural carbohydrates (Ward and Blaser, ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Cutting to 5 cm resulted in the highest yields in this system for both pure orchardgrass and the orchardgrass/alfalfa mixture over 3 years. It is clear that harvesting to a low cutting height will remove a greater proportion of aerial biomass and this has been shown in several experiments with orchardgrass where yields were greater at lower cutting heights (Brink et al., ; Mitchell, ; Raese & Decker, ; Sprague & Garber, ; Volesky & Anderson, ). Low cutting heights, however, remove a greater proportion of photosynthetic leaf area and non‐structural carbohydrates (Ward and Blaser, ).…”
Section: Discussionmentioning
confidence: 89%
“…Persistence of perennial grasses is defined as the ability of each tiller to produce on offspring annually such that members of the population replace themselves (Edwards & Chapman, ). Many studies use either tiller density (Raese & Decker, ; Volesky & Anderson, ) or per cent ground cover (Brink et al., ; Smith, Jaques, & Balasko, ) to determine the effects of various treatments on the persistence of swards. It is also known, however, that tiller density alone is not always related to the yield of swards (Davies, ).…”
Section: Introductionmentioning
confidence: 99%
“…Volesky et al (2010) reported that warm-season grasses usually have less total annual production because they do not actively grow during as much of the growing season as do coolseason grasses in Nebraska. These authors also considered that warm-season grasses cannot be made to grow at all during early spring and fall when soil and air temperatures are cool.…”
Section: Functional Groupsmentioning
confidence: 99%
“…Comparisons among studies can be difficult because of the differences in species, intensity and frequency of defoliation. Furthermore, responses are likely to change across climates, soil types, soil water and soil fertility conditions (Volesky and Anderson, 2007). For these reasons defoliation recommendations in general are difficult.…”
Section: Introductionmentioning
confidence: 99%